If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-3x=-64
We move all terms to the left:
-5x-3x-(-64)=0
We add all the numbers together, and all the variables
-8x+64=0
We move all terms containing x to the left, all other terms to the right
-8x=-64
x=-64/-8
x=+8
| -6x+14=74 | | 8(h−86)=72 | | 1/2x-9=2x+1 | | -11+x=-15 | | x2+2x-6x=0 | | 490=68x+14 | | -5k-1=-1-5k | | x/18–4=-6 | | 24-20n=144 | | 9n+36=54 | | 2n-27=229 | | |18|g-11=9(-2+11)+8|g | | 3.5x-(1.5x+3000)=3.5x-(1.52x+3000) | | 7a+1=3=18 | | (2x+5)=96 | | 3(p+2)=3(2p+4) | | 6(b−76)=96 | | (2x+8)×(5x-11)=x | | 8x=5x-36 | | 9(2n-1/3)-4=10 | | –9+2p=p | | 12+3x+x=2x-20 | | -2(3u-4)+4u=6(u+2) | | s−7–2=–1 | | 3c-12=-c+24 | | 4=3(v+2)-5v | | 2a+7=5a−5 | | –10d+9=–9d | | 7x+15=3x+4+4x | | 3(3y-7)=2y+7 | | 13x*12=1233 | | 4x+2=2x+6x+2 |